Starduck Roasted Cafe / Mohd Ebdazief Abrahim ... [et al.] - Abrahim, Mohd Abdazief; Sirat, Siti Noorsyafiqah; Jaafar, Fazilah; Hussin, Norasima; Basar, Nur Aishah (2013)
This business is based on partnership where it consists of five (5) members. The members consist of the General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial. The business capital is amounted to RM 133,670.00 where the total contribution by General Manager is RM 49,800.00, Administration Manager is RM 20,329.00, Marketing Manager is RM 21,999.00, Operation Manager is RM 21 ,262.00 and Financial Manager is RM 20,280.00. Starduck Roasted Cafe is a business related to the Halal duck. Our target market focus is for the people who like to try duck cuisine in Halal way. This is because it is very hard to find a halal duck in the market. So we would like to become a leader in producing a halal cuisine based on duck. Our business will be expected to open on 2013 and our vision is to be a successful and a wellknown cafe that provides halal duck dishes for people in Sabah by the year 2023. This will be realized by the full commitment and cooperation among the partners to achieve the vision of this business.